The Integrity of Editorial Cartoon Discourse - Widya Widya (Scope : Journal of English Language Teaching, 2017)
This study aims at analyzing the integrity of editorial cartoon discourse through the devices of cohesion and the patterns of coherence that appear in language and images. The method used in this study is a qualitative method. The results show that the relationship of language and images in the discourse helped to create the topic of each text. The connection between language and images is known from the role of language which gives information on the images, or vice versa, the images clarify things that are expressed through language. The amount of panel-to-panel transition which is higher than the amount of language cohesive devices indicates that in PR buat Presiden, the images play more important role than language in developing the integrity of discourse. The data show that without images, it is often difficult to understand the language. Key words: discourse, editorial cartoon, cohesion, coherence